2016
DOI: 10.1099/jgv.0.000424
|View full text |Cite
|
Sign up to set email alerts
|

Merida virus, a putative novel rhabdovirus discovered in Culex and Ochlerotatus spp. mosquitoes in the Yucatan Peninsula of Mexico

Abstract: Sequences corresponding to a putative, novel rhabdovirus [designated Merida virus (MERDV)]were initially detected in a pool of Culex quinquefasciatus collected in the Yucatan Peninsula of Mexico. The entire genome was sequenced, revealing 11 798 nt and five major ORFs, which encode the nucleoprotein (N), phosphoprotein (P), matrix protein (M), glycoprotein (G) and RNA-dependent RNA polymerase (L). The deduced amino acid sequences of the N, G and L proteins have no more than 24, 38 and 43 % identity, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Several closely related ISVs belonging to Rhabdoviridae comprise a phylogenetically divergent group and a major split between those infecting arthropods and other hosts (Bourhy et al , ; Vasilakis et al , ; Charles et al , ). This major phylogenetic division between Rhabdoviridae genera indicates that their biology is strongly influenced by mode of transmission and host species, as observed for other RNA viruses (Bourhy et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Several closely related ISVs belonging to Rhabdoviridae comprise a phylogenetically divergent group and a major split between those infecting arthropods and other hosts (Bourhy et al , ; Vasilakis et al , ; Charles et al , ). This major phylogenetic division between Rhabdoviridae genera indicates that their biology is strongly influenced by mode of transmission and host species, as observed for other RNA viruses (Bourhy et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, advances in DNA sequencing technology have allowed the identification of a wide range of novel viruses associated with mosquitoes (Aguiar et al, 2015; Auguste et al, 2014; Bolling et al, 2015; Carissimo et al, 2016; Chandler et al, 2015; Charles et al, 2016; Cholleti et al, 2016; Coffey et al, 2014; Contreras-Gutierrez et al, 2017; Fauver et al, 2016; Frey et al, 2016; Li et al, 2015a; Li et al, 2015b; Nasar et al, 2012; Ng et al, 2011; Palacios et al, 2015; Pauvolid-Correa et al, 2016; Shi et al, 2015; Simmonds et al, 2017; Vasilakis et al, 2014a; Wang et al, 2015). We examine here, by electron microscopy and metagenomics analysis, 11 mosquito derived viral isolates from the extensive collection of the World Reference Center for Emerging Viruses and Arboviruses (WRCEVA) (https://www.niaid.nih.gov/research/wreceva), whose morphology indicated the likely presence of multi-segmented reoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Merida virus is an unclassified Rhabdoviridae recently described from Culex spp. in Mexico (Charles et al, 2016).…”
Section: Resultsmentioning
confidence: 99%